Alamat ng rosas The legend of the rose - Matias, Segundo D.; Madueno, Ghani; Bravo, Becky; Garcia, Edith (Quezon City Lampara Publishing House, Inc., 2012)
"In the old days, there was a queen who was like no other in terms of beauty who lived happily with her husband the king. A rival king desired her and abducted her, while an envious witch desired to have her lovely face and cunningly took it from her. Find out in this story the origin of the rose--how great king Hulio's love was for Rosa, and how the rose got its thorns."
Stories with moral values
Text in Filipino and English.
Keywords: Roses -- Fiction; Roses -- Folklore